Impact of non-surgical periodontal therapy on serum Resistin and periodontal pathogen in periodontitis patients with obesity - Tahir, Khairunnisa Md; Ab Malek, Ainul Haliza; Vaithilingam, Rathna Devi; Saub, Roslan; Safii, Syarida Hasnur; Rahman, Mohammad Tariqur; Razak, Fathilah Abdul; Alabsi, Aied M.; Baharuddin, Nor Adinar (BioMed Central, 2020)
Background Non-surgical periodontal therapy (NSPT) known as gold standard treatment in managing periodontitis. The aim of this study was to investigate the response of NSPT in periodontitis subjects who were obese. Clinical parameters of periodontitis, changes in serum resistin and periodontal pathogens in subgingival plaque were compared before and after NSPT in periodontitis subjects who were obese and with normal weight. Methods A total of 48 periodontitis subjects (obese, n = 18; normal weight, n = 30) were recruited (hereafter will be referred as participants) to participate into a prospective, before and after clinical trial. Obesity status is defined by body mass index (BMI) criteria (obese: >= 30 kg/ m(2); normal weight < 25 kg/m(2)). Visible Plaque Index (VPI), Gingival Bleeding Index (GBI), Probing Pocket Depth (PPD) and Clinical Attachment Loss (CAL) were recorded; and serum and plaque were collected at baseline and following 12 weeks post-NSPT. Serum resistin level was analyzed using enzyme-linked immune-sorbant assay (ELISA), while detection of periodontal pathogens in dental plaque were carried out using real time PCR (qPCR). Results Following NSPT, means VPI and GBI showed significant improvement between obese and normal weight groups (p < 0.05), but no difference in means PPD and CAL was observed between groups. Obesity remained as a predictor for VPI and GBI after adjusting for smoking habit. No significant difference was observed in serum resistin level and mean counts for P. gingivalis, T. forsythia, and P. intermedia between obese and normal weight groups following NSPT. Conclusions Regardless of obesity status, NSPT has a significant impact on VPI and GBI in periodontitis subjects. However, the impact of NSPT towards serum resistin and periodontal pathogens was non-significant in those with periodontitis.